The blood glucose lowering effect of Malaysian Tinospora crispa in rats - SARAH FIRDAUSA; MAUNG MAUNG CHO; KHIN MAUNG MAUNG; NILAR AUNG; NORSIDAH KUZAIFAH; SURYAWATI SURYAWATI (Jurnal Natural, 2020)
Diabetes is defined as a chronic hyperglycemia which should be countered by the effective, safe and readily available hypoglycemic agents. Herbal is among alternatives that has been used by society for years but lacks of documented evidences. Tinospora crispa (TC) is enriched by phytochemicals which potentially reduce blood glucose thus is useful for diabetic patients. This study aimed to investigate the potency of TC inreducing blood sugar and body weight. It involved 30 healthy rats divided into 5 groups namely: normal control, normal fed with TC extract, diabetic, TC-treated diabetic (dose 500 mg/kg w/w), and vitamin E-traeted diabetic rats (60 IU). The body weight and fasting blood glucose were measured each week for 1 month. The administration of TC extract 500 mg/kg (w/w) helps to maintain body weight in diabetic rats and reduce the fasting blood glucose. TC is highly potent as hypoglycemic agents therefore needed to be explored further.